2014
DOI: 10.1161/circep.113.000850
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Longest Intrapatient Left Ventricular Electrical Delay May Predict Acute Hemodynamic Improvement in Patients After Cardiac Resynchronization Therapy

Abstract: Background-One of the reasons for patient nonresponse to cardiac resynchronization therapy is a suboptimal left ventricular (LV) pacing site. LV electric delay (Q-LV interval) has been indicated as a prognostic parameter of cardiac resynchronization therapy response. This study evaluates the LV delay for the optimization of the LV pacing site. Methods and Results-Thirty-two consecutive patients (23 men; mean age, 71±11 years; LV ejection fraction, 30±6%; 18 with ischemic cardiomyopathy; QRS, 181±25 ms; all mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 29 publications
4
94
1
Order By: Relevance
“…Theoretically, the site of latest activation should exhibit the most dyssynchrony and as such would represent an ideal pacing site. While some work appears to confirm the site of LEA is synonymous with the optimal pacing site [21], more recent analysis has shown optimal site exhibits late but not supremely delayed activation [100]. Sites demonstrating excessively delayed activity may in fact merely represent distal activation occurring within islands of non-viable tissue.…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)mentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, the site of latest activation should exhibit the most dyssynchrony and as such would represent an ideal pacing site. While some work appears to confirm the site of LEA is synonymous with the optimal pacing site [21], more recent analysis has shown optimal site exhibits late but not supremely delayed activation [100]. Sites demonstrating excessively delayed activity may in fact merely represent distal activation occurring within islands of non-viable tissue.…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)mentioning
confidence: 99%
“…Both of these studies retrospectively analyzed the degree of electrical latency at the site of LV lead deployment; however, Zanon et al evaluated whether Q-LV might be used to identify the optimal site in an individual patient by systematically screening all of the suitable coronary sinus (CS) veins [21]. A strong correlation was observed between Q-LV prolongation and improvements in acute hemodynamic response.…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)mentioning
confidence: 99%
See 1 more Smart Citation
“…36 Thus targeting the site of latest electrical activation, as defined by a QLV interval greater than the median of 95 ms, can improve patient response to CRT. Subgroup analyses from these trials show that this is a robust predictor of response, even among subjects with non-LBBB, ischaemic aetiology or QRS duration <150 ms.…”
Section: Electrical Dyssynchronymentioning
confidence: 99%
“…To improve the response rate of patients, the optimal location from which to pace the LV free wall has therefore received some interest. In earlier studies, it was found that the optimal location from which to pace the LV is in the non-ischemic, non-apical, postero-lateral/lateral regions of the LV epicardium, or the latest point of mechanical or electrical activation [4][5][6].The heart remodels in response to sustained pacing with regards to the anatomy, mechanics and electrophysiology properties [7,8]. New pacing catheter technologies such as multipole pacing (MPP) and multi-vein pacing (MVP) allow for the LV lead position to be altered post implant without further surgery.…”
mentioning
confidence: 99%